Inference generation in older adults: Comparing pictorial and textual comprehension in the context of cognitive decline. - Varkentin, Ekaterina; Brich, Irina R.; Sünkel, Ulrike; von Thaler, Anna-Katharina; Eschweiler, Gerhard W.; Huff, Markus (Memory & Cognition, 2026)
Narrative comprehension, a cognitive skill essential for social participation, relies on a range of abilities, including memory and inference-making. While aging-related cognitive changes are well-documented, research on narrative comprehension in aging populations yields mixed findings, underscoring the importance of this study. This preregistered study examines how age, education, and presentation format (i.e., the narrative's codality: pictorial vs. textual) influence inference generation in older adults (N = 143, ages 62–86 years). Participants were presented with pictorial and textual stories consisting of three panels, with the second panel replaced with a blank panel. Their task was to comprehend the stories and determine whether the inferences provided for the missing event were correct or incorrect. Results reveal that pictorial narratives were better comprehended than textual ones; however, this advantage attenuates with increasing age. Contrary to expectations, narrative comprehension was largely resilient to age-related declines, as neither age nor education significantly impaired performance. Exploratory analyses tested the influence of protective (e.g., physical and mental activity, companionship) and risk factors (e.g., depression, anxiety, chronic pain, stress, and poor sleep) but found no significant impact on comprehension. Notably, narrative comprehension correlated with memory performance but not with other cognitive abilities, underscoring its specificity within the broader cognitive domain. These findings highlight the stability of narrative comprehension across media and aging, while also suggesting a narrowing pictorial advantage with age. Implications for existing cognitive theories and future research directions are discussed.